Effect of octopamine manipulation on honeybee decision making: reward and cost differences associated with foraging. (February 2015) - Giray, Tugrul; Abramson, Charles I.; Chicas-Mosier, Ana; Brewster, Tiyi; Hayes, Christine; Rivera-Vega, Karianne; Williams, Maya; Wells, Harrington
Abstract : Neuromodulators have been shown to influence behavioural response in a context-dependent manner. To understand the nature of this effect we presented honeybee foragers with a foraging choice problem and fed them octopamine, its antagonist (mianserin), or simply sucrose (treatments). The test situation caused bees to deal with both cost variable (effort or work to reach the reward) and reward variable (sucrose molarity) problems simultaneously, where cost was varied by altering stamen length. High work (cost) was paired with a high reward, and low work was paired with a low reward, using blue versus white flowers as a colour cue. Regardless of treatment, roughly a third of the control bees maximized energy gain by choosing high-reward/high-work flowers (energy maximizers), but another third of the foragers consistently chose flowers that minimized work and consequently minimized reward (work minimizers). The remaining foragers seemed unable to solve the reward–cost problem and showed high fidelity to a flower colour (colour constant) even though doing so resulted in a change in cost and reward between experimental test phases. Ingestion of octopamine or its antagonist did not alter the frequency of each type of response in the forager population. However, error rate was altered in bees following energy maximization or work minimization strategies when ingesting octopamine or its antagonist. Although octopamine and mianserin affect the behaviour of honeybees, they do not appear to determine the foraging strategy of individuals. Highlights: We examined the influence of neuromodulators on foraging strategies of individual bees. Bees were colour constant, energy maximizers or work minimizers. Octopamine and its antagonist (mianserin) altered foraging behaviour but not the frequency of forager types. Ingestion of octopamine caused energy maximizers to make more mistakes. Ingestion of mianserin caused work minimizers to make fewer mistakes.